(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The consumer is a crucial factor in the promotion of any business. This paper is about consumers’ perception and intention on the deployment of differently-abled persons (DAP) in the Indian hospitality industry. The modified SERVQUAL model was used to study the consumers’ concern about accepting the services of DAP in the hospitality sector. Data was collected through a structured questionnaire in Google form among consumers all over the country, which was measured on a five point Likert scale to find out their choice of the inclusive Indian hospitality industry. A quantitative analysis reveals that consumers all over India have a positive attitude towards DAP staff, but neither they assuring of return business nor are they empathetic towards them. This work identified that the management of such organizations needs to be more strategic and adaptable. This paper represents original research that encourages hospitality businesses to employ DAP.